2021
DOI: 10.1038/s41420-021-00657-z
|View full text |Cite
|
Sign up to set email alerts
|

LHPP suppresses colorectal cancer cell migration and invasion in vitro and in vivo by inhibiting Smad3 phosphorylation in the TGF-β pathway

Abstract: The roles of phospholysine phosphohistidine inorganic pyrophosphate phosphatase (LHPP) in tumorigenesis have been recently proven in hepatocellular carcinoma (HCC), cervical, pancreatic, bladder, and thyroid cancers. Previous research demonstrated that LHPP repressed cell proliferation and growth by inactivating the phosphatidylinositol 3-kinase/AKT signaling pathway in vitro and in vivo. However, the functions and potential mechanisms of LHPP as a tumor suppressor in colorectal cancer (CRC) metastasis are sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…TGF-β is a multifunctional cytokine, and its receptors play a crucial role in cancer initiation and progression through a range of activities in the regulation of cell proliferation, differentiation, apoptosis, and migration ( Gencer et al, 2017 ). After activation of TGF-β signaling, TGF-β-associated ligands bind to corresponding receptors I and II ( de la Cruz-Merino et al, 2009 ) and then transfer extracellular signals to nuclear components through canonical TGF-β pathways, such as the TGF-β/Smad pathway, and noncanonical TGF-β pathways, such as the p38/mitogen-activated protein kinase (MAPK) pathway, GTP pathway, PI3K/AKT pathway, and NF-κB pathway ( Patil et al, 2011 ; Bataller et al, 2019 ; Chang and Pauklin, 2021 ; Choi et al, 2021 ; Hou et al, 2021 ). TGF-β has often been implicated in carcinogenesis, and studies have demonstrated that TGF-β has both oncogenic and tumor-suppressive functions in cancer regulation mechanisms ( Yu and Feng, 2019 ; Belitškin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β is a multifunctional cytokine, and its receptors play a crucial role in cancer initiation and progression through a range of activities in the regulation of cell proliferation, differentiation, apoptosis, and migration ( Gencer et al, 2017 ). After activation of TGF-β signaling, TGF-β-associated ligands bind to corresponding receptors I and II ( de la Cruz-Merino et al, 2009 ) and then transfer extracellular signals to nuclear components through canonical TGF-β pathways, such as the TGF-β/Smad pathway, and noncanonical TGF-β pathways, such as the p38/mitogen-activated protein kinase (MAPK) pathway, GTP pathway, PI3K/AKT pathway, and NF-κB pathway ( Patil et al, 2011 ; Bataller et al, 2019 ; Chang and Pauklin, 2021 ; Choi et al, 2021 ; Hou et al, 2021 ). TGF-β has often been implicated in carcinogenesis, and studies have demonstrated that TGF-β has both oncogenic and tumor-suppressive functions in cancer regulation mechanisms ( Yu and Feng, 2019 ; Belitškin et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The transforming growth factor‐β (TGF‐β) represents a structurally‐related protein family that comprises bone morphogenic proteins, activins/inhibins, and TGF‐β, while the latter controls various cellular functions such as apoptosis, proliferation, migration, epithelial–mesenchymal transition (EMT), and differentiation 14 . Interestingly, attenuation of the TGF‐β/Smad signalling was previously associated with repression of cancer cell EMT in hepatocellular carcinoma, in addition to diminishing cell invasion and migration in GC 15,16 . On the other hand, up‐regulation of the key proteins of the TGF‐β/Smad pathway has been documented in GC and further reported to exhibit a significant positive correlation with the degree of differentiation, lymph node metastasis, and Tumour–Node–Metastasis stage of GC 17 .…”
Section: Introductionmentioning
confidence: 99%
“…14 Interestingly, attenuation of the TGF-β/Smad signalling was previously associated with repression of cancer cell EMT in hepatocellular carcinoma, in addition to diminishing cell invasion and migration in GC. 15,16 On the other hand, up-regulation of the key proteins of the TGF-β/Smad pathway has been documented in GC and further reported to exhibit a significant positive correlation with the degree of differentiation, lymph node metastasis, and Tumour-Node-Metastasis stage of GC. 17 Ginsenoside Rb2 was previously indicated to inhibit EMT of colorectal cancer cells via blockade of the TGF-β1/Smad signalling.…”
mentioning
confidence: 99%
“…Our previous study also demonstrated that LHPP could repress the proliferation and progression of colorectal cancer cells by inhibiting PI3K/AKT pathway [ 15 ]. In addition, our team suggested that LHPP protein might impede the metastasis of colorectal cancer by mediating the phosphorylation of Smad3 in TGF-β/Smad canonical pathway [ 16 ]. Based on these results and references, we hypothesized that LHPP might be involved in the development of pancancer and play a common role in the progression of different cancer types.…”
Section: Introductionmentioning
confidence: 99%